Alzheimer's disease : insights into low molecular weight and cytotoxic aggregates from in vitro and computer experiments - molecular basis of amyloid-beta protein aggregation and fibril formation - Derreumaux, Philippe (Molecular medicine and medicinal chemistry., 2013)
Alzheimer's disease is the most common form of senile dementia, affecting more than 24 million people worldwide. It is characterised pathologically by abnormally high levels of neurofibrillary tangles resulting from the accumulation of tau protein in dead and dying neurons, and by elevated numbers of senile plaques in the cortex and hippocampus of the brain. The major component of senile plaques is a small protein of 39-43 amino acids called amyloid-? (A?). Thus far, no treatment has been shown to slow the progression of sporadic and familial Alzheimer's disease. A large body of evidence points.